Ceftriaxone‐induced radiation recall dermatitis. Issue 8 (9th April 2020) - Patel, Nirav V.; Samuels, Michael; Elsayyad, Nagy
Abstract: Background: Radiation recall dermatitis (RRD) is an acute inflammatory skin reaction occurring in a skin area previously exposed to radiotherapy and triggered by subsequent intake of a drug, most commonly a chemotherapeutic agent. RRD secondary to antibiotics has also been reported but is a rare phenomenon overall and there are no reports of RRD in association with ceftriaxone exposure. Methods: We report on a 59‐year‐old patient who had received radiotherapy to the neck bilaterally and who developed RRD 6 months later after a single dose of intramuscular ceftriaxone. Results: The patient's rash resolved without further intervention over the ensuing 2 days following administration of a single dose of ceftriaxone. Conclusion: This case illustrates that while RRD secondary to antibiotic exposure is rare, it is part of the differential diagnosis to be considered for acute dermatitis when there is a past history of radiotherapy to the same skin area.